The impact of genetic polymorphisms on the pharmacokinetics of efavirenz in African children. (25th April 2016) - Bienczak, Andrzej; Cook, Adrian; Wiesner, Lubbe; Olagunju, Adeniyi; Mulenga, Veronica; Kityo, Cissy; Kekitiinwa, Addy; Owen, Andrew; Walker, A. Sarah; Gibb, Diana M.; McIlleron, Helen; Burger, David; et al.
Abstract : Aims: Using a model‐based approach, the efavirenz steady‐state pharmacokinetics in African children is characterized, quantifying demographic and genotypic effects on the drug's disposition. Simulations are also conducted allowing prediction of optimized doses of efavirenz in this population. Methods: We modelled the steady‐state population pharmacokinetics of efavirenz in Ugandan and Zambian children using nonlinear mixed‐effects modelling. Individual mid‐dose efavirenz concentrations were derived and simulations explored genotype‐based dose optimization strategies. Results: A two‐compartment model with absorption through transit compartments well described 2086 concentration‐time points in 169 children. The combined effect of single nucleotide polymorphisms (SNPs) 516G>T and 983T>C explained 44.5% and 14.7% of the variability in efavirenz clearance and bioavailability, respectively. The detected frequencies of composite CYP2B6 genotype were 0.33 for 516GG|983TT, 0.35 for 516GT|983TT, 0.06 for 516GG|983TC, 0.18 for 516TT|983TT, 0.07 516GT|983TC and 0.01 for 516GG|983CC. The corresponding estimated clearance rates were 6.94, 4.90, 3.93, 1.92, 1.36, and 0.74 l h −1 for a 15.4 kg child and median (95% CI) observed mid‐dose concentrations 1.55 (0.51–2.94), 2.20 (0.97–4.40), 2.03 (1.19–4.53), 7.55 (2.40–14.74), 7.79 (3.66–24.59) and 18.22 (11.84–22.76) mg l −1, respectively. Simulations showed that wild‐type individuals had exposures at the bottom of therapeutic range, while slower metabolizers were overexposed. Conclusions: Dosage guidelines for African children should take into consideration the combined effect of SNPs CYP2B6 516G>T and 983T>C.